Archaeology essentials theories, methods, and practice - Renfrew, Colin 1937- (Thames & Hudson, 2008)
A guide to all aspects of archaeology, this work provides a readable and compact introduction to archaeology for those new to the field. Long-established techniques are carefully explained as well as exciting new methods as the authors describe the ways in which archaeologists seek to explain and interpret the remote past of humankind.